Media Exposure of Apple Growers about Recommended Apple Production Technology - Shah, Zahoor Ahmad; Dar, Mushtaq Ahmad; Maqbool, Showkat; Matoo, Jehangir Muzaffar; Shah, Umat Ul Fiza (Indian Journal of Extension Education, 2020)
Kashmir apple has lived up to its reputation for being one of the choicest fruits, and Kashmir has for long been considered as the home of apples. Kashmir valley is endowed with congenial agro-climatic conditions for a wide range of horticultural crops. The area and production has increased, but the productivity of apple fruit is not up to the mark despite of the fact that the climate in the region is conducive for apple cultivation. There could be various reasons for the low productivity of apple fruit and one of them is low level of media exposure of apple growers. The present study was conducted to study different aspects of media exposure of apple growers about recommended technologies of apple production. The study was conducted in three districts of Kashmir division selected purposively, having maximum area under apple cultivation. A multistage sampling procedure was adopted for the study. The data was collected during 2019. It was observed that majority of the apple growers in Shopian (54.46 %) and Baramula(53 %) were having medium level of media exposure and low level of media exposure was found in district Budgam (50 %).
Keywords: Apple; Exposure; Growers; Media; Technology